Cyano-B12 or Whey Powder with Endogenous Hydroxo-B12 for Supplementation in B12 Deficient Lactovegetarians - Naik, Sadanand (Nutrients, 2019)
Lactovegetarians (n = 35) with low vitamin B12 (B12) status were intervened for eight weeks capsules containing cyano-B12 (CN-B12), (2 × 2.8 µg/day), or equivalent doses of endogenous B12 (mainly hydroxo-B12 (HO-B12)) in whey powder. Blood samples were examined at baseline, every second week during the intervention, and two weeks post-intervention. The groups did not differ at baseline in [global median (min/max)] plasma B12 [112(61/185)] pmol/L, holotranscobalamin [20(4/99)] pmol/L, folate [13(11/16)], the metabolites total homocysteine [18(9/52)] µmol/L and methylmalonic acid [0.90(0.28/2.5)] µmol/L, and the combined indicator of B12 status (4cB12) [−1.7(−3.0/−0.33)]. Both supplements caused significant effects, though none of the biomarkers returned to normal values. Total plasma B12 showed a higher increase in the capsule group compared to the whey powder group (p = 0.02). However, the increase of plasma holotranscobalamin (p = 0.06) and the lowering of the metabolites (p > 0.07) were alike in both groups. Thereby, the high total plasma B12 in the capsule group was not mirrored in enhanced B12 metabolism, possibly because the B12 surplus was mainly accumulated on an “inert” carrier haptocorrin, considered to be of marginal importance for tissue delivery of B12. In conclusion, we demonstrate that administration of whey powder (HO-B12) or capsules (CN-B12) equivalent to 5.6 µg of B12 daily for eight weeks similarly improves B12 status but does not normalize it. We document that the results for plasma B12 should be interpreted with caution following administration of CN-B12, since the change is disproportionately high compared to the responses of complementary biomarkers.